Education Management in the Qur'an Perspective - Husnul Yaqin; Hasni Noor (Budapest International Research and Critics University, 2022)
This study aims to determine the management of education from the perspective of the Qur'an. This study uses a qualitative method with a literature study approach. The result of this research is that management is a process of utilizing all resources through other people and working with them. The process is in order to achieve common goals effectively, efficiently, and productively. The principles of educational management according to the Qur'an include sincerity, honesty, trustworthiness, fairness, responsibility, dynamic, practical, flexible, selective, effective and efficient, open, cooperative and participatory, giving warnings, giving instructions and directions. The conclusion of this research is henceforth, management functions like planning, organizing, mobilizing, and supervising. This function is a process that must be carried out by all parties involved in an organization. These functions will determine the success or failure of management performance.